Mitos Youkai dalam Komik Mokke Karya Takatoshi Kumakura - Karlina Devi, Ni Putu; Laksmita Sari, Ida Ayu; Pradana, Ngurah Indra (Humanis, 2017)
The title of this research is “The Myth of Youkai in Mokke Comics by Takatoshi Kumakura”. It focused on finding the description about the myth of youkai in Mokke comics, and the meaning of youkai in Japanese people faith. The Literary Anthropology theory by Endraswara and The Semiotics theory by Marcel Danesi were applied. As the result, various kinds of youkai with different descriptions were found. First, youkai that resembles a human, second, youkai tangible animals, and last youkai tangible objects. From the fourteenth youkai, there are youkai characters of good and evil were found .
Keywords: Youkai, Myth, Literary Anthropology, Semiotic